RESIKO BISNIS, PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN DAN STRUKTUR MODAL PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN - Jean Ivanka, Febrinka; Nurlaela, Siti; Suhendro, Suhendro (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
The research aims to test and find out whether there is an effect of bussiness risk, profitability, liquidity and firm size on capital structure in food and baverage sub-sector companies in 2014-2018. The object of this research is a food and baverage company listed on the Indonesia Stock Exchange in 2014-2018, totaling 26 companies. The technique used is purposive sampling. The samples used in this study were 12 food and baverage companies listed on the IDX. This research uses Multiple Linear Regression Analysis method. The results of this study indicate that the profitability and liquidity has affect the capital structure of food and baverage companies listed on the Indonesia Stock Exchange (BEI) in 2014-2018. While the bussiness risk and firm size have no effect on the capital structure of food and baverage companies listed on the Indonesia Stock Exchange (BEI) in 2014-2018.